1998
DOI: 10.1021/ma980113r
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Packing Disorder of Poly(p-phenylenebenzobisoxazole):  Structural Analysis by an Organized Combination of X-ray Imaging Plate System and Computer Simulation Technique

Abstract: To clarify the crystal structure of poly(p-phenylenebenzobisoxazole) (PBO) fibers, the analysis has been made for the X-ray diffraction data collected by the imaging plate system in combination with the computer simulation technique. The characteristic features of the X-ray diffraction pattern of PBO fiber are seen in the spotlike equatorial reflections and the diffuse reflections along the layer lines. The peak positions of the diffuse layer-line reflections were found to fit well to those of the molecular tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…We will give further explanation on this problem in the last section. One theory to explain why the crystal lattice starts to distort may be the microslippage due to weak interaction forces of neighboring molecules in the PBO crystal, 10 the onset of which may come from structural defects such as chain ends and the amorphous region in the fiber. Jones and Martin 21 reported that the PBO fiber modulus strongly depends on the concentration of molecular ends in the PBO crystal, which may support the above discussion.…”
Section: Hosemann's Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We will give further explanation on this problem in the last section. One theory to explain why the crystal lattice starts to distort may be the microslippage due to weak interaction forces of neighboring molecules in the PBO crystal, 10 the onset of which may come from structural defects such as chain ends and the amorphous region in the fiber. Jones and Martin 21 reported that the PBO fiber modulus strongly depends on the concentration of molecular ends in the PBO crystal, which may support the above discussion.…”
Section: Hosemann's Analysismentioning
confidence: 99%
“…There have been many studies to elucidate the secrets of PBO mechanical properties and morphological features. [5][6][7][8][9][10][11] One of the important structural features is that the fiber is composed of rigid-rod molecules that are highly oriented to the fiber axis. This molecular orientation improvement is made possible by the dry-jet wet spinning method together with heat treatment over 600°C under tension.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber can be spun from dope (concentrated solution) made from PBO molecules and poly-phosphoric acid, then coagulated, washed, dried and heat-treated if necessary. Because the PBO molecule take a relatively straight conformation in the fiber, the molecular orientation is proved to be very high along the fiber axis, whereas the interaction between molecules normal to the fiber direction is not so strong [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Therefore, the fiber shows relatively small crystallite size, especially along the a-and b-axes.…”
Section: Introductionmentioning
confidence: 99%
“…To improve this mechanical properties much higher, we have been looking into the structural formation of fiber during coagulation and found that a non-aqueous coagulant gives a different fiber structure 1 . The fiber is expected to have a higher molecular orientation with less structural inhomogeneity along the fiber axis, which has been revealed by small and wide-angle X-ray diffraction (SAXS and WAXS) techniques and high-resolution transmission electron microscope (HREM) observation [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Figure 1 shows the relationship between fiber modulus and the crystallite orientation of the (200) diffraction of the PBO crystal estimated by X ray, in which the three fibers show high molecular orientation to the fiber axis than other conventional fibers 19 .…”
Section: Introductionmentioning
confidence: 99%